Host-finding behaviour of female apple leaf curling midge, Dasineura mali Kieffer (Diptera: Cecidomyiidae) : a thesis presented in partial fulfilment of the requirements for the degree of Masters [i.e. Master] of Applied Science in Plant Health at Massey University, Palmerston North, New Zealand - Galanihe, Lalitha Damayanthi (Massey University, 1996)
In the past few years New Zealand populations of apple leaf curling midge, Dasineura mali Kieffer (Diptera: Cecidomyiidae) (hereafter referred to as ALCM) have exploded, making control in commercial apple orchards more difficult. The present studies were initiated to generate information about the basic biology and behaviour of adult female ALCM. Experiments were conducted in the laboratory during two consecutive summer seasons in 1994/95 and 1995/96 at Massey University, Palmerston North and at HortResearch, Mt. Albert Research Center, Auckland, respectively. The diel emergence patterns of adult ALCM males and females were synchronized. Adults of both sexes started emerging at 05.00 h, with approximately 95% of adults emerging before noon. Females exhibited calling behaviour (a posture associated with the release of sex pheromone) within minutes after emergence. After mating females ceased calling. When tested in a wind tunnel containing apple foliage, mated females were rarely active before 10.00 h. After this, greater numbers of females flew upwind and landed on apple foliage, with peak responses to apple foliage occurring after 14.00 h. When given a choice between apple and pear foliage, female ALCM oviposited four times more eggs on apple than on pear. However, when given no choice between plant species females oviposited similar numbers of eggs on the two plant species. Female ALCM laid more eggs on immature apple leaves and buds than on mature apple leaves. Chemical cues from apple foliage were found to be of major importance in the host-finding behaviour of ALCM females. Volatile chemicals from apple foliage triggered upwind flight, approach and landing. Volatile chemicals from a non-host plant, pear, stimulated only half as many females to fly upwind and rarely stimulated approach or landing. Females were more responsive to chemical stimuli from immature foliage of apple than to stimuli from mature foliage. A dichloromethane extract of apple leaves increased the percentages of females flying upwind and approaching extract treated filter papers six and thirty times, respectively, over filter papers treated with dichloromethane. Out of the females that flew upwind to apple foliar extracts, 48.7% landed and 23% exhibited post-landing plant-examination behaviours. No females landed on filter papers treated with dichloromethane.
Keywords: Dasyneura mali; New Zealand; Insects -- Host plants; Apples -- Diseases and pests; Control